Percepciones y actitudes de los ciudadanos residentes en Bogotá acerca del pago del impuesto al valor agregado -IVA- (2017)
This research paper presents the results of a quantitative research aimed at knowing the perceptions of the respondents about the payment of the Value Added Tax, VAT. From a theoretical perspective, the role of taxes in a society is related, as well as the evidence on some ways to evade them, as shown by the information collected. Through qualitative and quantitative analysis it is possible to demonstrate the effects that the perception of citizens has on tax payments and the effects this causes on the income of the population.From the preferences approach, the profile of the citizens who make their contribution, their payments and the effects of the evasion are identified. It is concluded that the failure to pay is associated with a variety of factors that motivate said behavior over time.